PENGARUH KEPERCAYAAN KONSUMEN, PERSEPSI KEAMANAN, PENGETAHUAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PADA LAYANAN FITUR SHOPEE MALL|ORI DI KELURAHAN MOJO KOTA SURABAYA - Bramasta Arief Rizky Priambada; Nekky Rahmiyati (Nirta Learning Centre, 2025)
This study aims to analyze the influence of consumer trust, security perception, and consumer knowledge on purchase decisions and customer satisfaction with Shopee Mall|Ori services in Mojo Subdistrict, Surabaya. The analysis method employed Partial Least Squares-Structural Equation Modeling (PLS-SEM), including descriptive analysis, validity and reliability tests, and path coefficient analysis (direct and indirect effects). Data were collected from 100 respondents who are users of Shopee Mall|Ori in Mojo Subdistrict. The results indicate that consumer trust does not significantly influence customer satisfaction but significantly affects purchase decisions. Security perception significantly influences both purchase decisions and customer satisfaction, while consumer knowledge significantly affects purchase decisions but not customer satisfaction. Purchase decisions mediate the relationship between security perception and consumer knowledge with customer satisfaction but do not mediate the relationship between consumer trust and customer satisfaction. This study recommends enhancing strategies focusing on security assurance, consumer education, and trust reinforcement. The research is limited by its specific location and cross-sectional design; thus, broader studies are suggested to enrich the findings.